Floating Drug Delivery System: A Promising Approach for Gastroprotective Drug Delivery - dakhil, Ibtihal Abdulkadhim; Noori, Mustafa M.; Ahmed, Dalya Isam (Journal of Pharmacology and Drug Development, 2025)
Floating Drug Delivery Systems (FDDS) is a very recent approach in the development of oral drug delivery systems, which can be employed to control the gastric emptying time of filled device for both sustained and controlled release (CR) preparations, to locate the CR in a particular site, to minimize the drug loss and to improve drug delivery. These types of systems have a low density, are buoyant in gastric fluid, maintain longer residence time in the stomach with controlled drug release. FDDS can be prepared in tablets, capsules, powders, granules, films and microspheres and are especially valuable when dealing with highly water-soluble drugs with short halflife, having absorption window low in the gut or having instability at intestinal pH. There are several types of FDDS such as effervescent, non-effervescent, raft-forming, the hydrodynamically balanced and the inflatable system that uses different ways to float and consequent modification of release. Their performance is highly dependent upon physiological parameters, such as gastric pH, motility, meal content, age, and body position. FDDS have various advantages such as increased bioavailability, rapid onset of action, a lower frequency of dose administration, better patient compliance, and long site-specific action in the stomach, which is useful in the case of gastroesophageal reflux disease (GERD) and peptic ulcers. Nevertheless, gastric emptying variability and complexity of the formulation still pose obstacles. Newer excipients and polymers and newer carriers will continue to improve these systems, making FDDS a potential weapon for future gastroprotective and controlled-release therapies.